Anticancer Compounds Based on Isatin-Derivatives: Strategies to Ameliorate Selectivity and Efficiency - Ferraz de Paiva, Raphael Enoque; Vieira, Eduardo Guimarães; Rodrigues da Silva, Daniel; Wegermann, Camila Anchau; Costa Ferreira, Ana Maria (Frontiers in Molecular Biosciences, 2021)
In this review we compare and discuss results of compounds already reported as anticancer agents based on isatin-derivatives, metallated as well as non-metallated. Isatin compounds can be obtained from plants, marine animals, and is also found in human fluids as a metabolite of amino acids. Its derivatives include imines, hydrazones, thiosemicarbazones, among others, already focused on numerous anticancer studies. Some of them have entered in pre-clinical and clinical tests as antiangiogenic compounds or inhibitors of crucial proteins. As free ligands or coordinated to metal ions, such isatin derivatives showed promising antiproliferative properties against different cancer cells, targeting different biomolecules or organelles. Metallation usually improves its biological properties, indicating a modulation by the metal and by the ligand in a synergistic process. They also reveal diverse mechanisms of action, being able of binding DNA, generating reactive species that cause oxidative damage, and inhibiting selected proteins. Strategies used to improve the efficiency and selectivity of these compounds comprise structural modification of the ligands, metallation with different ions, syntheses of mononuclear and dinuclear species, and use of inserted or anchored compounds in selected drug delivery systems.